Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the given system of equations by substitution, the process involves isolating one variable in one of the equations and substituting it into the other equation. Here's a detailed, step-by-step solution to determine the best variable and equation for substitution:
Given the system of equations:
1. [tex]\( x + 6y = 9 \)[/tex]
2. [tex]\( x - 10y = 13 \)[/tex]
### Step-by-Step Solution:
1. Consider isolating one variable:
- First equation: [tex]\( x + 6y = 9 \)[/tex]
- Second equation: [tex]\( x - 10y = 13 \)[/tex]
2. Solve for [tex]\( x \)[/tex] in the first equation:
- [tex]\( x + 6y = 9 \)[/tex]
- To isolate [tex]\( x \)[/tex], subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ x = 9 - 6y \][/tex]
3. Substitute [tex]\( x \)[/tex] from the first equation into the second equation:
- Second equation: [tex]\( x - 10y = 13 \)[/tex]
- Substitute [tex]\( x = 9 - 6y \)[/tex]:
[tex]\[ (9 - 6y) - 10y = 13 \][/tex]
4. Simplify and solve for [tex]\( y \)[/tex]:
- Combine like terms:
[tex]\[ 9 - 16y = 13 \][/tex]
- Subtract 9 from both sides:
[tex]\[ -16y = 4 \][/tex]
- Divide both sides by -16:
[tex]\[ y = -\frac{1}{4} \][/tex]
### Conclusion:
From the detailed steps, the best way to solve this system is to isolate [tex]\( x \)[/tex] in the first equation [tex]\( x + 6y = 9 \)[/tex] and then substitute it into the second equation [tex]\( x - 10y = 13 \)[/tex].
Thus, the best variable to solve for is [tex]\( \mathbf{x} \)[/tex], and the best equation to solve from is the [tex]\(\mathbf{first \ equation}\)[/tex].
Answer: [tex]\( \boxed{\text{B. } x, \text{ in the first equation}} \)[/tex]
Given the system of equations:
1. [tex]\( x + 6y = 9 \)[/tex]
2. [tex]\( x - 10y = 13 \)[/tex]
### Step-by-Step Solution:
1. Consider isolating one variable:
- First equation: [tex]\( x + 6y = 9 \)[/tex]
- Second equation: [tex]\( x - 10y = 13 \)[/tex]
2. Solve for [tex]\( x \)[/tex] in the first equation:
- [tex]\( x + 6y = 9 \)[/tex]
- To isolate [tex]\( x \)[/tex], subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ x = 9 - 6y \][/tex]
3. Substitute [tex]\( x \)[/tex] from the first equation into the second equation:
- Second equation: [tex]\( x - 10y = 13 \)[/tex]
- Substitute [tex]\( x = 9 - 6y \)[/tex]:
[tex]\[ (9 - 6y) - 10y = 13 \][/tex]
4. Simplify and solve for [tex]\( y \)[/tex]:
- Combine like terms:
[tex]\[ 9 - 16y = 13 \][/tex]
- Subtract 9 from both sides:
[tex]\[ -16y = 4 \][/tex]
- Divide both sides by -16:
[tex]\[ y = -\frac{1}{4} \][/tex]
### Conclusion:
From the detailed steps, the best way to solve this system is to isolate [tex]\( x \)[/tex] in the first equation [tex]\( x + 6y = 9 \)[/tex] and then substitute it into the second equation [tex]\( x - 10y = 13 \)[/tex].
Thus, the best variable to solve for is [tex]\( \mathbf{x} \)[/tex], and the best equation to solve from is the [tex]\(\mathbf{first \ equation}\)[/tex].
Answer: [tex]\( \boxed{\text{B. } x, \text{ in the first equation}} \)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.